OPTIMAL SIZING AND ENVIRONMENTAL IMPACT ASSESSMENT OF LITHIUM BATTERY ENERGY STORAGE SYSTEM IN AN ELECTRICAL DISTRIBUTION NETWORK WITH LARGE PHOTOVOLTAIC POWER PENETRATION IN PALESTINE - Jaradat, Tha'er (An-Najah National University, 2025)
This work evaluates the integration of lithium-ion battery energy storage systems (BESS) into Palestine’s fragmented power grid, focusing on environmental, technical, and economic dimensions. A multi-method framework combines life cycle assessment (LCA), techno-economic optimization, and market attractiveness analysis. Using ReCiPe 2016 methodology in openLCA, lithium-ion iron phosphate batteries (LFP) demonstrated the lowest environmental burden, with a 89% reduction in global warming potential (GWP) when charged via photovoltaic (PV) systems versus grid electricity. Linear optimization for a 25 MVA/33 kV network with 7 MWp PV capacity identified an optimal BESS size of 120 Ah/33 kV, achieving a 1% loss of load probability (LOLP) and annual savings of $0.367 million. The BESS market attractiveness index (BMAI) revealed Palestine’s score (1.907) lags behind regional peers like Turkey (2.964) and Israel (2.729), hindered by weak policies and limited storage infrastructure. Key contributions include: (1) a novel integration of LCA with grid-specific optimization to balance sustainability and reliability; (2) development of the BMAI for cross-country energy storage market benchmarking; and (3) actionable policy pathways, such as hybrid PV-BESS incentives and recycling programs, to align Palestine’s energy transition with regional advancements. This work underscores the viability of BESS systems for reducing emissions, enhancing grid resilience, and advancing energy security in politically constrained environments.
التحجيم الأمثل والأثر البيئي لمنظومات بطاريات الليثيوم في شبكة توزيع كهربائية تحتوي على منظومات كهروضوئية كبيرة في فلسطين